FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA PARE KEDIRI TAHUN 2020 - Susanti, Ami; Solikah, Mar’atus; Winarko, Sigit Puji (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this research is to know taxpayer compliance, e-filing implementation system, level of tax understanding and taxpayer awareness in primary tax service office pare kediri. This study uses a quantitative approach that is casual associative. The data used is primary data. The procedure used in the collection of this data is through observation and direct interview on the research object. The results of this study showed that partially taxpayer compliance, the application of the e-filing system, the level of tax understanding and taxpayer awareness have an effect on the tax server office (KPP) Pratama Pare Kediri and simultaneously taxpayer compliance, the application of the e-filing system, the level of tax understanding, and taxpayer awareness influenced the tax service office (KPP) Pratama Pare Kediri. There have been many studies that examine about taxpayer compliance, e-filing implementation system, level of tax understanding and taxpayer awareness, but each study has its own characteristics related to the title, place and results of research. Both in terms of the causes of weakness and obstacles that have been passed through. And researchers believe that if different places of research are reformed.